Strategi Pemberdayaan Ekonomi Lokal Melalui Penguatan Permodalan Umkm Berbasis Prinsip Ekonomi Syariah - Muhamad Ilham Maulana; Muhammad Rasyid Abdul Ghafir; Naufal Muhammad Dzakwan; Uswatun Hasanah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This study aims to identify and examine local economic empowerment strategies through strengthening capital financing for Micro, Small, and Medium Enterprises (MSMEs) producing traditional Bengkulu souvenirs based on Islamic economic principles. A mixed methods approach was applied involving 120 MSMEs located in three major districts of Bengkulu, namely Central Bengkulu, Seluma, and Kaur. Primary data were collected through structured questionnaires with a validity score of 0.84 and a reliability score of 0.91, as well as in-depth interviews with business owners and representatives of Islamic financial institutions. Data analysis employed descriptive statistics, multiple regression, and thematic analysis to examine the relationship between Islamic financing factors, including musyarakah, mudharabah, ijarah, and wakalah, and business performance measured by revenue growth, job creation, and product sustainability. The results indicate that the musyarakah financing model had the most significant effect on increasing revenue (β = 0.42; p < 0.001) and job creation (β = 0.35; p < 0.01). In addition, trust in Islamic financial institutions and product compatibility with local cultural values were identified as important moderating factors. This study concludes that Islamic economic-based financing strategies, particularly through musyarakah schemes, can serve as effective instruments for empowering the local economy of Bengkulu traditional souvenir MSMEs while simultaneously strengthening the integration of socio-cultural values with ethical financial principles. The policy implications of this study include the development of specialized Islamic financing products for the traditional culinary sector and the enhancement of the capacity of regional Islamic financial institutions